2000
DOI: 10.1099/00221287-146-11-2865
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific PCR shows that genetic exchange occurs among genetically diverse Nodularia (Cyanobacteria) filaments in the Baltic Sea

Abstract: Some cyanobacteria have been shown to exchange genetic information under laboratory conditions, but it has not been clear whether such genetic exchange occurs in the natural environment. To address this, a population genetic study was carried out on the filamentous diazotrophic cyanobacterium Nodularia in the Baltic Sea. Nodularia filaments were collected from 20 widely distributed sampling stations in the Baltic Sea during June and July 1998. Allele-specific PCR (AS-PCR) was used to characterize over 2000 fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 32 publications
6
61
2
Order By: Relevance
“…The STRR fingerprints of N. spumigena showed that the Baltic Sea population is not clonal. The result is in agreement with previous studies on noncoding regions, such as the 16S-23S rRNA ITS, gvpA-IGS and phycocyanin operon intergenic spacer (PC-IGS) (Barker et al, 1999(Barker et al, , 2000Laamanen et al, 2001). These studies revealed variation among Baltic N. spumigena strains sharing identical 16S rRNA genes.…”
Section: Phylogenetic Relationships Within the Genus Nodulariasupporting
confidence: 82%
“…The STRR fingerprints of N. spumigena showed that the Baltic Sea population is not clonal. The result is in agreement with previous studies on noncoding regions, such as the 16S-23S rRNA ITS, gvpA-IGS and phycocyanin operon intergenic spacer (PC-IGS) (Barker et al, 1999(Barker et al, , 2000Laamanen et al, 2001). These studies revealed variation among Baltic N. spumigena strains sharing identical 16S rRNA genes.…”
Section: Phylogenetic Relationships Within the Genus Nodulariasupporting
confidence: 82%
“…The taxonomic assessment of Type 1 was another problem, although it resembled Nodularia baltica in heterocyst morphology, the latter being transversely oval to almost spherical and wider than vegetative cells. Further observations indicated that the tightly coiled filaments assigned to Type 1 could be statistically distinguished from Type 2 using our discriminant function .Our aim was, therefore, to show an application of the image analysis-based method we developed in order to estimate filamentous cyanobacterial biomass in mixed-species natural assemblages.Population genetic analysis of Nodularia partially carried out over the same area and period revealed that 3 out of the 12 allele-combinations distributed across the Baltic Sea were much more frequent than others (Barker et al 2000a). These data suggest a correlation between the 3 genotypes and the 3 morphotypes observed by us.…”
supporting
confidence: 60%
“…Recombination has also been observed in populations of Nodularia from the Baltic Sea (Barker et al, 2000). It has been suggested that the observation of genealogical concordance among groups but not within may provide an operational proxy for the application of the biological species concept (Dykhuizen & Green, 1991;Dettman et al, 2003).…”
Section: Discussionmentioning
confidence: 87%